Vacuum infusion process. - Cocquyt, André (Jumby Bay Studios, 2002)
This DVD is laid out in three modules giving an overview of the vacuum infusion process (VIP) technology at different levels. Module one (certification level, beginner) addresses the technology in general. Anyone with a bit of GRP background will be able to start using the VIP technology. Module two (certification level, operator), provides an introduction of shop floor instruction of VIP, with lots of details and hands on tips about how to use VIP in the production of fiberglass parts. Module three (certification level, technician) is oriented toward the technician and/or engineer who have to design, implement and manage the technology.